2015
DOI: 10.1089/jpm.2014.0053
|View full text |Cite
|
Sign up to set email alerts
|

Development of the CASH Assessment Tool To Address Existential Concerns in Patients with Serious Illness

Abstract: Our quality improvement project demonstrated that the CASH assessment tool is useful in ascertaining existential concerns of patients with serious illness. It enhances patient care by the primary team as well as the palliative care team. As a brief set of questions with an easy-to-remember mnemonic, the CASH assessment tool is feasible for a busy palliative consult service. Furthermore, the positive results of this project merit more rigorous evaluation of the CASH assessment tool in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…There are some tools available to identify existential distress in such patients (Newell et al, 2002;Alesi et al, 2015;Benito et al, 2014). In recent years, new psychological interventions have been put forward for these patients, including methods of seeking meaning and reinforcing the patient's sense of dignity (Chochinov et al, 2002b;Breitbart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some tools available to identify existential distress in such patients (Newell et al, 2002;Alesi et al, 2015;Benito et al, 2014). In recent years, new psychological interventions have been put forward for these patients, including methods of seeking meaning and reinforcing the patient's sense of dignity (Chochinov et al, 2002b;Breitbart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The advanced stage of incurable disease processes affects the perception or feeling of dignity that a patient holds about themselves (Chochinov, 2007; Chochinov et al, 2002 a ; Hack et al, 2004). There are some tools available to identify existential distress in such patients (Newell et al, 2002; Alesi et al, 2015; Benito et al, 2014). In recent years, new psychological interventions have been put forward for these patients, including methods of seeking meaning and reinforcing the patient's sense of dignity (Chochinov et al, 2002 b ; Breitbart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Five studies described the development of instruments to help identify spiritual distress ( Table 5). The instruments were validated in specific patient populations, including older adult inpatient rehabilitation, 29,30 patients with cancer admitted to an oncology unit, 23 patients assessed by the palliative care consult team, 45 and patients with advanced cancer in a palliative care unit. 50 None of the articles identified in our search described instruments to identify spiritual distress among family members of patients in acute care or hospice.…”
Section: Themesmentioning
confidence: 99%
“…A report of a quality improvement initiative described the CASH existential assessment tool, a mnemonic with each letter reflecting the core objective of a question (Care, Assistance/help, Stress, Hopes/fears). 45 The questions were intended to identify existential issues related to meaning, identity, autonomy, dignity, support, connectedness, relationships, stress, anxiety, guilt, isolation, hope, fear, and anxiety. CASH was integrated into dialogueoriented palliative care consults and evaluated through a brief survey of referring physicians and the palliative consultants who administered the CASH assessment.…”
Section: Themesmentioning
confidence: 99%
“…In 2013, Luchetti et al, conducted a systematic review of tools and identified and provided an overview of dialogueoriented tools in medical practice [10]. Up to 2015, the database search led to the identification of three additional tools [15][16][17]. These, together with the tools identified by Luchetti et al, were reviewed for clinical setting, structure, themes and questions.…”
Section: Literature Searchmentioning
confidence: 99%